DOAJ.
Directory of Open Access Journals. DOAJ is a unique and extensive index of diverse open access journals from around the world, driven by a growing community, committed to ensuring quality content is freely available online for everyone. All DOAJ services are free of charge including being indexed. All data is freely available.
Keywords: Nieuws; Tijdschriftartikels